The Sociolinguistics of Hashtag #Socialdistancing On Instagram As The Prevention Toward COVID-19 - Diana Anggraeni; Yetsyah Priastika Yudha; Dini Wulansari (Publikasi Indonesia, 2021)
As the characteristic of time is to keep moving forward or unrepeatable, we never know that the alteration of the language is the same as the mechanism of time. In this circumstance, this paper purposed to take place as a clarification of the polemics that keep happening time by time. A debate questioned different perspectives against the contextuality of the hashtag #socialdistancing through the Instagram post against the COVID-19 prevention. The hashtag #socialdistancing is out of context toward the COVID-19 prevention, in which it is a cherry-picked use of the word. This is also supported by how the social influence blindly supports the mistake rooted through public posts such as Instagram’s post. This paper is purposely created to clarify the social phenomena against the language alteration undergone in the wrong way through the use of the hashtag #socialdistancing as the prevention. This study uses a qualitative descriptive method to analyse the data since the data is uncountable and cannot be handled by the quantitative method. The misguided use of the hashtag itself has changed the language understanding amongst the public, especially the Instagram user, which will create another loop of language error in the future. Furthermore, this will result in the social stratification of the language use that will be created without noticing the point of creating it, also the transformation of the word social and distance beyond the track-record that has been undergone previously.